Algorithm project weight calculation aircraft - Абрамова, Г. В.; Конотоп, Д. І. (Proceedings of National Aviation University (archive), 2013)
The paper describes the process of a complex technical object design on the example of the aircraft, using information technology such as CAD/CAM/CAE-systems, presents the basic models of aircraft which are developed in the process of designing and reflect the different aspects of its structure and function. The idea of control parametric model at complex technical object design is entered, which is a set of initial data for the development of design stations and enables the optimal complex technical object control at all stages of design using modern computer technology. The paper discloses a process of weight design, which is associated with all stages of development aircraft and its production. Usage of a scheduling algorithm that allows to organize weight calculations are carried out at various stages of planning and weighing options to optimize the use of available database of formulas and methods of calculation